Perencanaan dan Perancangan Fasilitas Sirkuit Road Race - Yosi Valentina Simorangkir; Anton Topan; Theresia Widi Asih Cahyani (Musamus Journal of Architecture, 2020)
Merauke has a lot of potential racing talent but the lack of racing facilities to channel the interests and talents of young people in Merauke has an impact on wild racing, racing activities carried out on roads and beaches that endanger safety and comfort and road racing events held in Merauke still use Open space such as a highway with facilities as is, it is necessary to support the road race circuit supporting the racing activities, as well as the racing circuit track according to national standards of 1.2km. Techno Artistic architectural approach is applied to the use of fabrication materials, energy efficient technology. The results of the design of road race circuit facilities are equipped with regional and building utility installations, so that the results of this design do not damage the surrounding environment and safety on the site.